(untitled) (Al-Qamar, 2020)
This research compares Watt’s and Spencer’s interpretations of The Quran. The trend of interpretation of The Holy Qur’an seems very common all across the world. The study adopts qualitative descriptive and analytical research methods. A systematic analysis of the views of both scholars in the light of traditional Islamic Qur’ānic tafsīr sciences has been done. The analysis demonstrates that both commentaries do not satisfy the requirements of the Islamic sciences of Qur’ānic interpretation. Both commentaries are not comprehensible and faithful to the source text and fulfill the demands of the target readers only. The research insists on purpose-based interpretation of The Holy Quran in the light of Islamic sciences of tafsīr.